What can livestock breeders learn from conservation genetics and vice versa? - Kristensen, Torsten N.; Hoffmann, Ary A.; Pertoldi, Cino; Stronen, Astrid V. (Frontiers in Genetics, 2015)
The management of livestock breeds and threatened natural population share common challenges, including small effective population sizes, high risk of inbreeding, and the potential benefits and costs associated with mixing disparate gene pools. Here we consider what has been learnt about these issues, the ways in which the knowledge gained from one area might be applied to the other, and the potential of genomics to provide new insights. Although there are key differences stemming from the importance of artificial versus natural selection and the decreased level of environmental heterogeneity experienced by many livestock populations, we suspect that information from genetic rescue in natural populations could be usefully applied to livestock. This includes an increased emphasis on maintaining substantial population sizes at the expense of genetic uniqueness in ensuring future adaptability, and on emphasizing the way that environmental changes can influence the relative fitness of deleterious alleles and genotypes in small populations. We also suspect that information gained from cross-breeding and the maintenance of unique breeds will be increasingly important for the preservation of genetic variation in small natural populations. In particular, selected genes identified in domestic populations provide genetic markers for exploring adaptive evolution in threatened natural populations. Genomic technologies in the two disciplines will be important in the future in realizing genetic gains in livestock and maximizing adaptive capacity in wildlife, and particularly in understanding how parts of the genome may respond differently when exposed to population processes and selection.